PENERAPAN MODEL FLIPPED CLASSROOM BERBANTUAN VIDEO PEMBELAJARAN TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA - Wiwin Karimah (Universitas Pekalongan, 2018)
The PBL model used by the teacher in learning mathematics in SMP N 2 Karanganyar is considered unable to solve problems in class. The teacher has involved students in learning, students are required to conduct interviews and observation activities in the field. Teacher expectations with these activities, students can get used to solving math problems in class. But when students are given different problems, students have not been able to make the solution. Flipped Classroom is an alternative learning model that can overcome these problems. This study aims to determine (1) whether students' mathematical problem solving abilities through the flipped classroom model can achieve KKM, (2) students' mathematical problem solving abilities using the flipped classroom model are better than students' mathematical problem solving abilities using the PBL model. This type of research is a quasi-experimental. The instrument used in this study is a test. Analysis of the data in this study using the proportion test and t test. The results of this study indicate that: (1) the problem-solving ability through the flipped classroom model can achieve KKM, (2) the problem-solving ability of students with the flipped classroom model is better than the PBL model.